Three essays on international trade - CHEN, Renjing (Institutional Knowledge at Singapore Management University, 2021)
In the first chapter, we develop an estimation procedure to identify the partial (direct) effects of the GATT/WTO membership on variable and fixed trade costs, respectively. This procedure extends the techniques of Anderson and Van Wincoop (2003) on the structural relationship of multilateral resistance terms and of Helpman, Melitz and Rubinstein (2008) on the structural modeling of trade incidence. We then develop a general equilibrium framework (that allows for the presence of zero trade) to simulate the impact of variable, fixed, and total trade cost changes on the firm-level trade structure (including the bilateral export productivity cutoff, the weighted/unweighted extensive margin of export, the intensive margin, and the mass of active firms), the bilateral trade flow, and the aggregate welfare due to the GATT/WTO system (given the trade cost effects estimated in the first stage) for the period 1978–2015. Information asymmetry can create substantial frictions when importing firms find it difficult to acquire information about foreign products. In the second chapter, I use detailed China Customs Data to show that firms tend to import from countries with which they already have an importing relationship. Motivated by this fact, I develop a dynamic model describing firms’ decisions on their choice of sourcing country. This model incorporates both communication cost and satisfaction uncertainty, which are lower with familiar countries than with unfamiliar ones. Using this model, I estimate the benefits of importing from familiar countries measured by the probability improvement of receiving satisfactory products. I find that this probability can be improved by a maximum of 89.0 percent when importing from familiar countries instead of from unfamiliar ones. These results also support the prediction that the effective unit cost of intermediates is lower when importing from familiar countries. The third chapter presents a heterogeneous firm model à la Melitz (2003) in which firms suffer from both the agency problem internally and financial constraints externally. We show that conditional on the same raw productivity draw, managers of potential exporting firms around the export cutoff in financially underdevelopedcountries exert more effort than their counterparts in financially developed countries, as to induce their owners to export. This finding has very positive policy implications, as firms in financially underdeveloped countries can compete with their peers in financially developed countries by exerting more managerial effort. We find clear empirical evidence for this theoretical prediction using the World Management Survey data for more than 7,000 firms in 20 countries during 2002-2012.